The Contingent Claims Approach to Corporate Vulnerability Analysis : Estimating Default Risk and Economy-Wide Risk Transfer - Xiao, Yingbin; Gapen, Michael; Gray, Dale.; Lim, Cheng (Washington, D.C. : International Monetary Fund, 2004)
In this paper, we examine the ability of the contingent claims approach (CCA) to identify corporate sector and economy-wide vulnerabilities. We apply the Moody's MfRisk model, which uses aggregated CCA principles, to assess vulnerabilities retroactively in two historical country cases. The results indicate that the method may prove helpful in identifying corporate sector vulnerabilities and estimating the associated value of risk transfer across interrelated balance sheets of the corporate, financial, and public sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet